(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
A preliminary study was conducted to estimate cost and return analysis on yam cultivation at Gaidghat of Bagharpara upazila of Jashore from February to March 2021. The average yam cultivation area was 0.12 ha in the study area. Different types of yam were cultivated in the study area, which had excellent local names, such as LalJhupi, KaloJhupi, Gorai, Lalteer, Altapat, Munshi, etc. Yam seed was shown from April to May and harvested from December to March. Most of the farmers planted yam seeds in rows where plant to plant distance was 1.5-2.5 feet and line to line distance was 2-3 feet. Average number of plants per hectare was 17023 nos., and the seed required 851 kg ha-1. The total cost of yam production was Tk. 1,23,060 ha-1, where the variable cost was Tk. 69,579 ha-1 (56.54%) and fixed cost were Tk. 53,481 ha-1 (43.46%). Yield of yam tuber was 44.98 ton ha-1, and seed yam was 2.05 ton ha-1. Gross return was Tk. 1,75,097 ha-1, gross margin was Tk. 1,05,518 ha-1 and the net return was Tk. 52,037 ha-1. The benefit cost ratio was 2.52, which means it’s a profitable crop. Some disease organisms like fungi, viruses, and mites affect yam. Int. J. Agril. Res. Innov. Tech. 13(1): 72-76, June 2023